2020
DOI: 10.1155/2020/1834525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the AB0 Blood System and Proximal Femoral Fracture Patterns in the Turkish Population

Abstract: Objective. AB0 blood groups have shown to be associated with increased risk of several orthopedic disorders such as Achilles tendon rupture and hip osteoarthritis. The objective of this study was to investigate relationships between the AB0 blood system and hip fracture patterns, duration of hospitalization, and amount of blood transfusion. Methods. Data of 308 patients treated due to hip fractures in our hospital between 2017 and 2019 were evaluated. Epicrisis reports and X-rays of the patients included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In England, the blood group distribution of Groups A, B, O, and AB is 45%, 9%, 43% and 3%, respectively [9]. The Italian Blood Donation Association reported that the national distribution of Groups A, B, O, and AB is 32.02%, 14.10%, 50.63% and 3.25%, respectively [10]. Li et al reported the Guangzhou Blood Centre control group to be 27.3% group A, 26.5% group B, 38.4% group O and 7.8% group AB [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In England, the blood group distribution of Groups A, B, O, and AB is 45%, 9%, 43% and 3%, respectively [9]. The Italian Blood Donation Association reported that the national distribution of Groups A, B, O, and AB is 32.02%, 14.10%, 50.63% and 3.25%, respectively [10]. Li et al reported the Guangzhou Blood Centre control group to be 27.3% group A, 26.5% group B, 38.4% group O and 7.8% group AB [8].…”
Section: Discussionmentioning
confidence: 99%
“…Blood group A is common in the Turkish population. According to the data of 5 million people reported by the Turkish Red Crescent, blood group distribution is as follows: A: 42.5%, B:15.8%, O: 32.2%, and AB:7.6% [10]. In a study on 288,469 subjects by Ergün et al, conducted in a similar location to that of the current study, the blood group rates were found to be as follows: A: 44.62%, B: 15.45%, O: 32.24%, and AB: 7.69% [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations